Rotor vibration control using tilting-pad journal bearing with active pads — Numerical and experimental results. (3rd March 2023) - Silva, H.A.P.; Nicoletti, R.
Abstract: Rotating machines are elements of great importance to the production chain, and they can eventually operate under unpredicted or off-the-norm conditions, thus causing failure and significant economic losses. One way of reducing the consequences of such off-the-norm operation of these machines is the modification of the characteristics of the bearings that support the rotor. Active bearings can be a solution to this problem because they can change the dynamic characteristics of the machine during operation without needing machine stops. The present work presents a tilting-pad journal bearing whose pads are controlled by electromagnetic actuators (an innovative design solution). By mounting the electromagnetic actuators in the bearing casing behind the pads, one can exert electromagnetic forces on the pads and make them change their angular position about the bearing. Hence, one can modify the dynamic characteristics of the rotor-bearing system for desired and more appropriate values for a given operational condition, thus reducing the need for machine stops and the consequent economic losses. In this work, we present the system in a test rig designed for the system's proof of concept, and both numerical and experimental results are provided for open- and closed-loop operating conditions. The bearing and the rotor are modeled by rigid-body dynamics, and the lubricant interface is modeled by the Reynolds equation. The dynamics of the electromagnetic actuators are identified experimentally and used in the model as an empirical model. A proportional–derivative controller is adopted in the closed-loop conditions. The results show the effectiveness of the system in reducing the lateral vibrations of the rotor during operation, and one observed a good correlation between the numerical and the experimental results. Graphical abstract: Highlights: Active bearing combining lubrication support and electromagnetic actuation. Tilting-pad bearing with electromagnetic actuators to control the motion of the pads. Experimental results show a high specific control capacity of the active bearing. Up to 28% reduction of vibration amplitude using proportional–derivative controller. Proposed model presents good correlation to the experimental results.